Study of an Indirect Injection (IDI) Diesel Engine Using Pure Coconut Oil, Pure Tamanu Oil and B-20 for Smart Microgrid Applications Part II: Pilot Testing - Iman Kartolaksono Reksowardojo; Aji Ardiansyah; Tobat Martin Leonardo; Dini Permatasari; Yuli Setyo Indartono; Fariza Almira Ghany (Mesin, 2023)
The Smart Microgrid (SMG) can be used as a solution to overcome problems with electrical distribution on remote islets. The SMG system allows for a combination of conventional and renewable energy for power generation. Biofuel was chosen as a renewable energy source because of its abundant availability and ease of mobilization. This study examined the performance of B-20, Pure Tamanu Oil (PTO), and Pure Coconut Oil (PCO) in an IDI diesel engine that acts as a backup for SMG systems in the Karimunjawa Islands. The entire SMG system consists of: diesel engine, stabilizer, inverter, PV, batteries, ice maker, and a channel to the electrical grid. The results show that PTO has the highest value of thermal efficiency, that of 17.38%, but with a higher BSFC of 0.54 kg/kWh when compared to B-20 usage (14.69% and 0.51 kg/kWh). According to performance test results, their performance can be compared to the first part of this twin paper, which is laboratory testing, with a range of 2400-3200 W loads. Therefore, it can be said that biofuels are feasible for replacing B-20, as shown in pilot testing.